Chemo‐ and Regioselective Catalyst‐Controlled Carbocyclization of Alkynyl Ketones: Rapid Synthesis of 1‐Indanones and 1‐Naphthols. Issue 32 (10th May 2019) - Song, Liangliang; Tian, Guilong; Van der Eycken, Erik V.
Abstract: A catalyst‐controlled intramolecular carbocyclization of 2‐alkynyl aryl ketones is presented. Under rhodium(III) catalysis, 1‐indanones are formed through 5‐ exo ‐ dig carbocyclizations with exclusive chemo‐, regio‐ and stereoselectivity. When catalyzed by copper(I), 1‐naphthols are obtained through 6‐ endo ‐ dig carbocyclizations with exclusive chemo‐ and regioselectivity. Abstract : Indeed, the catalyst matters : A catalyst‐controlled 5‐ exo ‐ dig and 6‐ endo ‐ dig carbocyclization of 2‐alkynyl aryl ketones for the rapid synthesis of 1‐indanones and 1‐naphthols with exclusive chemo‐, regioselectivity is reported.